التداولية بين الأتجاه اللساني وتحليل الخطاب - عرابى، غالية Orabi, Ghaliah; ميلود، عزوز (المركز الجامعي الونشريسي تيسمسيلت - مخبر الدراسات النقدية والأدبية المعاصرة, 2018)
Pragmatics is defined as the study of linguistic accomplishment during use, i.e., the study of language when used in different situational layers, considering it as specific words from specific speaker, and addressed to a specific discourse, by a specific term in a specific situation to achieve a specific communicative purpose whether that language is a text or speech. The latter-speech- is more indicative of the use and utilization of the text. It is based on the study of the effective use of language through tactual speakers in effective situations. In tight of this, our research aims at disclosing the pragmatic dimensions in the literary discourse in accordance with the theory of the acts of speech, which Searle and Austin laid down it foundations as well as utterances as performed speeches. In addition to the argumentative which is considered as an inducement of the recipient to what is displayed to him with a view to achieve a purpose. Hence we wonder, what are the pragmatic dimensions represented in? And to what extent can their procedures be at the level of the discourses?
تعرف التداولية بأنها دراسة المنجز اللغوي أثناء الاستعمال، أي دراسة اللغة عند استعمالها في الطبقات المقامية المختلفة، باعتبارها كلاما محددا صادرا من متكلم محدد، وموجها إلي خطاب محدد، بلفظ محدد في مقام محدد لتحقيق غرض تواصلي محدد، سواء أكانت تلك اللغة نصا أم خطابا، هذا الأخير – الخطاب – الذي يعتبر أكثر دلالة على الاستعمال والاستخدام من النص، إذ يقوم على دراسة الاستعمال الفعلي للغة، من خلال متكلمين فعليين في مقامات فعلية. وعلى ضوء هذا يهدف بحثنا إلى كشف الأبعاد التداولية في الخطاب الأدبي وفق أسس نظرية أفعال الكلام، التي أرسى دعائمها سيرل (searl) وأوستين (Austin)، وكذا الملفوظية باعتبارها خطابات مؤداة، بالإضافة إلى الحجاج الذي يعتبر استمالة للمتلقي لما يعرض عليه بغية تحقيق غاية. من هنا نتساءل: فيم تتمثل الأبعاد التداولية اللسانية؟ وإلى أي حد يمكن أجرأتها على مستوى الخطابات؟
Keywords: الأدب العربى -- الخطاب الأدبى -- الألفاظ اللغوية -- التداولية اللسانية